Women's adversities - Guimarães, Ana Paula (2022)
Published: 05/12/2021 It is up to the State to promote appropriate measures to “guarantee fundamental rights and freedoms and the respect for the principles of a democratic law State”, in accordance with Article 9 (b) of the Constitution of the Portuguese Republic. Our objectives were to examine how the Portuguese legislator is attentive to the particularities of being a woman in matters such as hygiene, health, motherhood and parental education during the execution of sentences and we wanted to investigate the mechanisms triggered by the State for protection, as a preventive measure, of women as victims of crimes. We made research, in numerical terms, to know the rate of constituted women accused in criminal proceedings, as well as the number of convicted, from a set of recent and of reference official documentary sources, based on the existing statistical resources. We also made an analysis of the pertinent legislative diplomas, among them, the aforementioned Code of the Execution of Penalties and Freedom Deprivation Measures and the General Regulation of Prison Establishments. The fulfilment of a prison sentence implies vast and varied consequences, from personal to familiar, passing through social and professional consequences, among others. We concluded that compared to the male universe, the number of women accused and convicted is clearly lower. On the other hand, it is women who make up the largest share as victims of certain offenses. According to the 2019 Annual Report, authored by APAV, female victims amounted to 8,394.